It is the truth that is therapeutic: a conversation with James Janko, author of Buffalo Boy and Geronimo*. Issue 4 (1st October 2016) - Jacobs, Beth
ABSTRACT: This narrative perspective describes a dialog that occurred over email and in person between the author of the novel Buffalo Boy and Geronimo and a nonfiction writer and therapist interested in the therapeutic aspects of writing. The novel derives from James Janko's experiences in Viet Nam, as a medic in the army and much later, as a person trying to understand and reclaim his earlier experiences of the land. The language of therapy falls short in describing how writing this moving and beautiful novel impacted the life of the author, but in retrospect he does see a therapeutic value of his writing.